2013
DOI: 10.1111/jzs.12013
|View full text |Cite
|
Sign up to set email alerts
|

Contributions to molecular systematics of water scavenger beetles (Hydrophilidae, Coleoptera)

Abstract: Phylogenetic relationships within Hydrophilidae were examined by analyses of separate and combined nuclear and mitochondrial markers (28S rRNA, 18S rRNA, 16S rRNA, 12S rRNA, COI and COII genes). The preferred (Bayesian) tree topology suggests a sister group relationship between Spercheidae and Hydrophilidae, supporting the ‘hydrophilid lineage’; Epimetopidae are placed on the base of the ‘helophorid branch’, the monophyly of Sphaeridiinae is highly supported, nested deeply within Hydrophilidae closest to Enoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…The results of the phylogenetic analysis based on all six genes are largely in agreement with earlier molecular studies (Bernhard et al, 2006;Bruvo-Mađarić et al, 2013). Some results are also in agreement with morphology-based studies (e.g., Hansen, 1991;Archangelsky, 1998;Beutel, 1999), such as the monophyly of Hydrophiloidea s.str., and the monophyly of Hydrophilidae and its subfamily Sphaeridiinae (e.g., Hansen, 1991;Bernhard et al, 2009).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The results of the phylogenetic analysis based on all six genes are largely in agreement with earlier molecular studies (Bernhard et al, 2006;Bruvo-Mađarić et al, 2013). Some results are also in agreement with morphology-based studies (e.g., Hansen, 1991;Archangelsky, 1998;Beutel, 1999), such as the monophyly of Hydrophiloidea s.str., and the monophyly of Hydrophilidae and its subfamily Sphaeridiinae (e.g., Hansen, 1991;Bernhard et al, 2009).…”
Section: Discussionsupporting
confidence: 80%
“…The enigmatic monospecific New Zealand genus Horelophus, for instance, is deeply nested within the traditional Hydrophilinae (in Chaetarthriinae sensu Short and Fikáček, 2013), suggesting that its subfamily rank (Hansen, 1991) is not justified phylogenetically. Like in Short and Fikáček (2013) and earlier studies (e.g., Bernhard et al, 2009;Bruvo-Mađarić et al, 2013) it was confirmed that monophyletic Sphaeridiinae are nested within a paraphyletic hydrophiline lineage (s. Hansen, 1991) which also includes Horelophus.…”
Section: Discussionsupporting
confidence: 53%
“…This implied the comparatively species‐poor sphaeridiine lineage was not as successful as its aquatic sister clade, which contains more than twice as many described species. Our data, as well as other recent studies (Bernhard et al ., , ; Mađarić et al ., ), suggest that the sphaeridiine lineage is highly nested within the Hydrophilinae. This turns the prior pattern of diversification on its head, as the sphaeridiine lineage, with nearly 1000 described species, is now placed as one of the last to diverge and sister to the Acidocerinae, which contains only c .…”
Section: Discussionmentioning
confidence: 99%
“…Korte et al, 2004;Bernhard et al, 2006) and the first total evidence analysis (Bernhard et al, 2009). Nevertheless, studies that followed Hansen (1991) lacked broad sampling of hydrophilid lineages: of the 19 family-group clades, the greatest number to be included in any single analysis was 11 (Archangelsky, 2004); no molecular analysis to date has included more than nine (Madarić et al, 2013). Additionally, many enigmatic family-group lineages have never appeared in any post-Hansen analysis (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The water scavenger beetles, family Hydrophilidae, are the largest group of the superfamily Hydrophiloidea comprising 173 genera and about 3000 species all over the world (Fikáček, Gentili, & Short, 2010;Mađarić, Stanković, Čorak, Ugarković, & Komarek, 2013;Bloom, Fikáček, & Short, 2014). The family is classified in six subfamilies; Hydrophilinae, Chaetarthriinae, Enochrinae, Acidocerinae, Rygmodinae and Sphaeridiinae.…”
Section: Introductionmentioning
confidence: 99%